Global optimization of grillages - Belevičius, Rimantas; Šešok, Dmitrij (Lietuvos matematikos rinkinys, 2023)
Important problem in civil engineering is obtaining optimal pile placement schemes for grillage-type foundations in order to reduce the number of piles and reactive forces arising in piles. The idealizations of problem and formulation for local and global optimization are discussed, highlighting the must for global optimization. The grillage is discretized using finite element method. Sensitivity of objective function is obtained analytically. The solution technology for a class of aforementioned problems is proposed based on the use of global optimization algorithms of package GAMS, which are implemented as ``black boxes”. Results of computational experiments are presented.
Keywords: optimization of grilage-type foundations; global optimization; finite element method